Barton Highway Improvement Strategy. - Transport for NSW (Chippendale, N.S.W. : Transport for NSW, 2017)
"This Barton Highway Improvement Strategy has been prepared in partnership with the Australian and NSW governments. The Improvement Strategy sets out the NSW Government's 20 year plan to manage and guide the development of the road corridor within NSW to improve safety, traffic efficiency and sustainability." --Executive summary (page ii).
Logo of NSW Government --Title screen.
Title from title screen.
Mode of Access: Available online.
Keywords: Highway planning -- Australia -- New South Wales; Highway planning -- New South Wales; Roads -- Design and construction -- New South Wales; Roads -- Australia -- New South Wales -- Design and construction; Traffic engineering -- Australia -- New South Wales; Traffic engineering -- New South Wales; Highway planning; Roads -- Design and construction; Traffic engineering; Barton Highway (N.S.W. and A.C.T.); New South Wales; Electronic books